Controlled comparison of cimetidine and carbenoxolone sodium in gastric ulcer. Issue 6174 (19th May 1979) - La Brooy, S J; Taylor, R H; Hunt, R H; Golding, P L; Laidlaw, J M; Chapman, R G; Pounder, R E; Vincent, S H; Colin-Jones, D G; Milton-Thompson, G J; Misiewicz, J J
Abstract : Fifty-four outpatients with endoscopically diagnosed benign gastric ulcer were allocated at random to treatment with either cimetidine 800 mg daily for six weeks or carbenoxolone sodium 300 mg daily for one week then 150 mg daily for five weeks. Ulcers were reassessed by endoscopy at the end of the trial. The endoscopist was unaware of the treatment and did not take part in the clinical care of the patients. Twenty-one of the 27 patients (78%) given cimetidine and 14 of the 27 (52%) given carbenoxolone had healed ulcers. Symptomatic response occurred earlier with cimetidine but was not significantly better. Unwanted effects were more common in the carbenoxolone group: 12 patients developed hypokalaemia, four of whom needed oral potassium supplements. The results suggest that histamine H2-receptor blockade is at least as effective as carbenoxolone sodium for benign gastric ulcer and produces fewer side effects.